2011
DOI: 10.2135/cropsci2010.09.0553
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping of Fall Armyworm Resistance in Zoysiagrass

Abstract: Molecular tools have not identified markers for host-plarit resistance to fall armyworm [Spodoptera frugiperda (J. E. Smith)], one of the most damaging insect pests in turfgrasses in the southeastern United States. Available quantitative trait loci (QTL) in maize {Zea mays L.) have further not been assessed for utility as comparative martcers for the trait across related taxa. This study reports a linkage map of the region conferring major control of fall armyworm resistance in zoysiagrass {Zoysia spp.). One g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Breeding objectives for zoysiagrasses are mainly to improve heat and drought tolerance, winter hardiness, disease and insect resistance. Several genetic maps of zoysiagrasses have been constructed to map targeted traits (Yaneshita et al ., ; Cai et al ., , ; Li et al ., , ; Jessup et al ., ). However, all current maps are partial, and the markers used in the previous studies, such as restriction fragment length polymorphism (RFLP) and amplified fragment length polymorphism (AFLP), are difficult to transfer between different mapping populations from one study to the next and are not suitable for integration of genetic maps with genome sequences.…”
Section: Introductionmentioning
confidence: 97%
“…Breeding objectives for zoysiagrasses are mainly to improve heat and drought tolerance, winter hardiness, disease and insect resistance. Several genetic maps of zoysiagrasses have been constructed to map targeted traits (Yaneshita et al ., ; Cai et al ., , ; Li et al ., , ; Jessup et al ., ). However, all current maps are partial, and the markers used in the previous studies, such as restriction fragment length polymorphism (RFLP) and amplified fragment length polymorphism (AFLP), are difficult to transfer between different mapping populations from one study to the next and are not suitable for integration of genetic maps with genome sequences.…”
Section: Introductionmentioning
confidence: 97%
“…Quantitative trait loci mapping for turfgrass has mainly been focused on disease and stress tolerance, and reproductive development related traits in ryegrass ( Lolium perenne L.), zoysiagrass ( Zoysia japonica Steud. ), and St. Augustinegrass [ Stenotaphrum secundatum (Walter) Kuntze; Forster et al, 2004; Ding et al, 2010; Jessup et al, 2011; Mulkey et al, 2014]. To date, no QTL mapping for establishment rate in bermudagrass has been reported.…”
mentioning
confidence: 99%
“…A high-density SSR genomic map has been completed (Li et al, 2009(Li et al, , 2010. Additionally, markers have been identified that are linked to a locus for fall armyworm (Spodoptera frugiperda) resistance (Jessup et al, 2011). Although 1044 SSRs have been developed for zoysiagrass (Cai et al, 2005), most are not publicly available (Jessup et al, 2011); however, a small number of zoysiagrass SSRs have been developed and released (Tsuruta et al, 2005).…”
mentioning
confidence: 99%